How Internet Accessibility Influences Household Expenditure: Findings from the National Socio-Economic Survey (SUSENAS) : English - Wibowo, Bintang Satrio; Fredericho Mego Sundoro, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to examine the impact of internet ownership on the level of consumption or expenditure among the Indonesian population, with a particular focus on household patterns. The study will utilize SUSENAS data as secondary data and as a sample for this research. We employ multiple linear regression using the Ordinary Least Square (OLS) method to capture the relationship between internet ownership and expenditure or consumption levels. The results indicate that internet ownership has a positive and significant relationship with individual expenditure or household spending. It is hoped that this study will provide insights into the importance of digitalization, particularly in terms of equal access to the internet for economic activities.